(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
Executive compensation has been one of the most controversial topics in recent years. There are two unstoppable trends in this field. On the one hand, the incentives design is evolving from models that consider only financial objectives towards a broader approach influenced by the Corporate Social Responsibility framework that takes into account environmental and social measures. On the other hand, and as a consequence of the new theoretic framework, all recent Codes of Conduct are enforcing the need for transparency. In this article, we analyze the path towards transparency in the case of Spain and the new Annual Remuneration Report that has been approved for all public listed companies.